The Impact of Parental Norms on Money Management (Literatur Review): Literature Review - Yuliani Yuliani; Surianti Surianti; Mohdari Mohdari; Ela Elliyana (ProBisnis : Jurnal Manajemen, 2023)
This study aims to provide information related to the influence of parental norms on money management; qualitative methods with literature survey techniques seek to place, obtain, read, and evaluate research literature. Analysis and search for articles involving themes with titles, abstracts, and keywords related to parental norms, money management, and financial socialization agents. Selection of compositions according to writing needs, list of documents, and type of article. The data collection technique in this study was a literature survey collected from the database using Harzing's Publish or Perish (PoP). The study results show that parents are very influential in shaping children's financial management behavior. Technically, parents are role models for children in shaping their financial management behavior